2023
DOI: 10.1245/s10434-023-14192-x
|View full text |Cite
|
Sign up to set email alerts
|

Research Priorities in Prehabilitation for Patients Undergoing Cancer Surgery: An International Delphi Study

Abstract: Background Recently, the number of prehabilitation trials has increased significantly. The identification of key research priorities is vital in guiding future research directions. Thus, the aim of this collaborative study was to define key research priorities in prehabilitation for patients undergoing cancer surgery. Methods The Delphi methodology was implemented over three rounds of surveys distributed to prehabilitation experts from across multiple spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This study was successful in enabling both experts by experience (people with lived experience of cancer) and experts by profession (professionals with a role in prehabilitation services) to create and reach consensus on the criteria based on values, objectives and aims for prehabilitation delivery and care. Previous Delphi studies on prehabilitation have focused mainly on the input of healthcare professionals with a role in prehabilitation (37,38), although the inclusion of patients in future studies has been strongly recommended (37). This study has produced criteria that include 60 statements organised within seven categories (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This study was successful in enabling both experts by experience (people with lived experience of cancer) and experts by profession (professionals with a role in prehabilitation services) to create and reach consensus on the criteria based on values, objectives and aims for prehabilitation delivery and care. Previous Delphi studies on prehabilitation have focused mainly on the input of healthcare professionals with a role in prehabilitation (37,38), although the inclusion of patients in future studies has been strongly recommended (37). This study has produced criteria that include 60 statements organised within seven categories (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by heterogeneity in interventions, target patient groups, and outcome measures. The top three research priorities in prehabilitation listed in an international Delphi study were: the effects of prehabilitation on surgical outcomes; identifying populations most likely to benefit from prehabilitation; and the optimal composition of prehabilitation programmes 54 . Concerning the first priority, a core outcome set could be helpful 55 .…”
Section: Future Directions Of Prehabilitationmentioning
confidence: 99%
“…Therefore, conducting randomized clinical trials to generate prospective data firstly on the efficacy, which is yet to be proven in patients with DTC, and then effectiveness of prehabilitation in this patient cohort would provide the strongest evidence for the increased uptake and acceptance in the field. The need for clear research priorities to inform the design of future prehabilitation trials has been recognized in a recently published international Delphi study [ 126 ]. The top research priorities in prehabilitation for patients undergoing cancer surgery identified by a panel of prehabilitation experts included the effect of prehabilitation on surgical outcomes, identifying populations most likely to benefit from prehabilitation and optimal composition of prehabilitation programs [ 126 ].…”
Section: Proposed Solutions To Increase the Uptake Of Prehabilitationmentioning
confidence: 99%
“…The need for clear research priorities to inform the design of future prehabilitation trials has been recognized in a recently published international Delphi study [ 126 ]. The top research priorities in prehabilitation for patients undergoing cancer surgery identified by a panel of prehabilitation experts included the effect of prehabilitation on surgical outcomes, identifying populations most likely to benefit from prehabilitation and optimal composition of prehabilitation programs [ 126 ]. In the absence of randomized clinical trials, healthcare providers may consider establishing a small independent study using existing study protocols and practical tips from other researchers.…”
Section: Proposed Solutions To Increase the Uptake Of Prehabilitationmentioning
confidence: 99%